Ocular manifestations of skin diseases with pathological keratinization abnormalities - Zdebik, Alexander; Zdebik, Natalia; Fischer, Matthias (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
Keratinization means cytodifferentiation of keratinocytes turning into corneocytes in the stratum corneum. Disorders of keratinization (hyperkeratosis, parakeratosis and dyskeratosis) are causing many dermatological diseases, including various types of ichthyoses, pachyonychia congenita, pityriasis rubra pilaris, all subtypes of psoriasis, pityriasis lichenoides, dyskeratosis congenita, leukoplakia and keratosis follicularis, which apart from skin lesions may affect the eye’s adnexae causing ectropion, entropion, blepharitis, madarosis, and trichiasis, the ocular surface causing keratitis, conjunctivitis, corneal ulceration and episcleritis, which in turn cause uveitis and various fundoscopic changes (proliferative retinopathy, retinal vasculopathy, macular oedema and birdshot chorioretinopathy). Knowledge of ocular symtoms associated with pathological keratinization is crucial, preventing sight-threatening complications such as corneal perforation, lagophthalmus, phthisis bulbi, retinal neovascularization, retinal vasculopathy and optic nerve atrophy. This review encourages dermatologists to monitor patients for ocular symptoms and encourage ophthalmologists to monitor patients for dermatological symptoms.